Effectiveness of ICT interventions for Diabetes: A Systematic Overview (protocol) - Bagayoko, Cheick Oumar; Anne, Abdrahamane; Gagnon, Marie-Pierre; Geissbuhler, Antoine (Journal of Health Informatics in Africa, 2018)
Background and Purpose: The use of Information and Communication Technologies (ICT) in fighting diabetes is particularly booming in recent years. Previous studies showed to varying degrees the impact that these technologies can have in the prevention and management of diabetes. The main objective of this overview of systematic reviews is to systematically summarize the best evidence on ICT interventions that can significantly improve one or more indicators of diabetes Methods: We will include all type of reviews that aim to evaluate the effect of ICTs on diabetes indicators. We will consider all types of ICT applications, including: mobile health, teleconsultations, tele-expertise, electronic health records, decision support systems, elearning etc. Key comparisons will be: ICT intervention for the management of diabetes versus no intervention; ICT intervention compared to the usual management of diabetes; ICT for the management of diabetes compared to other non-ICT interventions; ICT intervention versus another ICT intervention for the management of diabetes. We will include systematic reviews published in English and French during the past 25 years, i.e. between January 1991 and March 2015. Reviews will be limited to those on human subject only. Two reviewers will screen independently the title and abstract of the papers in order to assess their eligibility, and extract relevant information based on a predetermined grid. Any disagreements will be resolved first by discussion and consensus between the two reviewers, or will imply a third author as arbitrator. Results: Outcomes of interest will be clinical indicators of diabetes that could be influenced by ICT interventions. These will be the main non-exhaustive and objectively measurable indicators related to the monitoring and the management of diabetes and which are generally accepted by diabetes experts Conclusion: Based on concrete interventions that have demonstrated scientific evidence, this overview could help identify the most effective ICT interventions for improving diabetes indicators.